Short Communication: Acute toxicity effects of titanium nano particle TiO2 NPs on hematological indices in Goldfish (Carassius auratus, Linnaeus 1758) - ALIAKBAR HEDAYATI; FATEMEH DARABITABAR; SHAYDA AHMADVAND; SHARAREH AHMADVAND (Smujo International, 2017)
Hedayati A, Darabitabar F, Ahmadvand S, Ahmadvand S. 2017. Short Communication: Acute toxicity effects of titanium nano particle TiO2 NPs on hematological indices in Goldfish (Carassius auratus, Linnaeus 1758). Nusantara Bioscience 9: 152-155. Metal nanoparticles which include particles manufactured from metal oxides such as zinc oxide ZnO and titanium oxide TiO2 particles are broadly used due to their inimitable attributes such as diversity level chemistries and can be prepared into a variety of figures and sizes. The aim of this study was to investigate the effect of different TiO2 NPs concentrations on hematology indices in Goldfish (Carassius auratus). 105 goldfish with average total lengths of 6.50 ± 0.43 cm were used in this present study. Goldfish were exposed to a lethal concentration of 50% LC50 nano-titanium dioxide for a period of 0 (control), 24, 48 and 96h static toxicity examination, presented in tanks of 60L. The results of this study shows LC5096h nano titanium dioxide for goldfish is 19985±2.27 ppm and MAC value or the maximum allowable concentration calculated for this toxin is 1998 mg/L. No mortality observed in the control group. Fish exposed to nano-titanium dioxide for 7 days, a significant change in hematological (Hb, MCH, MCHC, MCV, RBC), and immunological (WBC) indices concentrations toward the control groups (p<0/05). The results of this study showed, however, LC50 of nano titanium dioxide was very high that means it doesn’t have much mortality effect, but it has negative effect on blood indices in goldfish and reduces red blood cells and hemoglobin in fish, eventually caused the death of fish.